The effect of the COVID-19 pandemic on disgust sensitivity in a sample of UK adults - Carr, Peter; Breese, Emily; Heath, Christopher J.; McMullan, Rachel (Frontiers in Public Health, 2022)
The COVID-19 pandemic led to the introduction of a range of infection prevention and control (IPC) measures that resulted in dramatic changes in people's lives however these IPC measures are not practiced consistently across the population. One predictor of an individual's responses to the pandemic is disgust sensitivity. Understanding how disgust sensitivity varies within the population could help to inform design of public health messages to promote more uniform behavioral change during future pandemics. To understand the effect of the current COVID-19 pandemic on an individual's pathogen disgust sensitivity we have compared pathogen disgust sensitivity during the current COVID-19 pandemic to baseline pathogen disgust sensitivity, determined prior to the COVID-19 pandemic, in the same sample of UK adults. We find that the COVID-19 pandemic did not alter overall pathogen disgust sensitivity suggesting that disgust sensitivity is stable despite IPC measures, public health messaging, media coverage and other factors associated with the COVID-19 pandemic.